The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00192-011-1609-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting anal sphincter defects: the value of clinical examination and manometry

Abstract: Clinical assessment has a poor sensitivity for detecting anal sphincter defects. The proposed manometric cut-off values can be used to either reassure or identify women who may need further assessment by EAU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…IAS defects have been independently correlated with severe anal incontinence symptoms. These results concur with those of previous studies, highlighting the importance of the accurate diagnosis of IAS injuries and adequate repair. Structured hands‐on training workshops have been shown to improve a doctor's ability to identify and repair OASIS.…”
Section: Discussionsupporting
confidence: 84%
“…IAS defects have been independently correlated with severe anal incontinence symptoms. These results concur with those of previous studies, highlighting the importance of the accurate diagnosis of IAS injuries and adequate repair. Structured hands‐on training workshops have been shown to improve a doctor's ability to identify and repair OASIS.…”
Section: Discussionsupporting
confidence: 84%
“…18 Additionally, a prospective cohort found an increased risk of anal sphincter injury if the PBL was < 3 cm. 19 However, another study found that PBL and pelvic floor muscle strength were not predictive of sphincter trauma, 20 and prospective data from a nulliparous cohort of women at our institution demonstrated no correlation between antepartum PBL and perineal tearing. 9 …”
Section: Discussionmentioning
confidence: 68%
“…It has been indicated that a short PBL is related to sonographic anal sphincter defects, 19 which are correlated to postpartum FI in some studies 12,20 but ultrasound findings are inconsistent predictors of postpartum FI pathology. 21,22 This indicates that anatomic changes, or even damage, do not always result in poor function.…”
Section: Discussionmentioning
confidence: 99%
“…This is disputed by Hallan et al , 22 who found DRE to be statistically equal in ability to ARM at predicting anal tone. In contrast, the study of Eckardt and Kanzler 21 suggests a higher sensitivity (ranging from 68% to 84%) and lower specifi city (57%), comparable with Roos et al , 25 who found the sensitivity of DRE to be 67% and specifi city 55% and proposed that manometry has a greater accuracy in detecting anal defects. The majority of the literature therefore fi nds DRE results to be inconsistent in accuracy and therefore not a reliable tool.…”
Section: Accuracymentioning
confidence: 64%